Antimicrobial activity of Kaempferia galanga against plant pathogen on rice - WORO SRI SUHARTI; ETIK WUKIR TINI; DINA ISTIQOMAH (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Suharti WS, Tini EW, Istiqomah D. 2023. Antimicrobial activity of Kaempferia galanga against plant pathogen on rice. Biodiversitas 24: 1320-1326. Rhizoctonia solani J.G.Kühn and Xanthomonas oryzae are two main pathogens in rice plants that cause sheath blight and bacterial leaf blight disease. Controlling these two diseases using plant extracts is an alternative, environmentally friendly method. Plant extracts are known to have the ability to inhibit microbial growth. The purpose of this study was to determine the ability of Kaempferia galanga L. (aromatic ginger) extract to inhibit the growth of R. solani and X. oryzae in-vitro and to determine the antimicrobial compounds contained in the extract. First, K. galanga was extracted using a maceration technique with 96% ethanol. Next, followed by an antifungal test on R. solani with a diffusion well technique and an antibacterial test with a disc agar technique against X. oryzae using two types of solvents (water and 96% ethanol) to obtain a concentration gradient (2, 4, 6, 8, and 10%). Then, the content of K. galanga compounds was examined using GC-MS. The results showed that K. galanga could inhibit the growth of pathogenic fungi and bacteria, as indicated by the formation of an inhibition zone. Chemical compounds such as 2-propenoic acid, 3-(4-methoxyphenyl)-, and ethyl ester are the dominant compound in K. galanga. In addition, several compounds with antimicrobial activity were found in the K. galanga extract, including germacrene-D, 1,8-cineol, borneol, caryophyllene, jasmone, and heptadecane.